2014
DOI: 10.1038/aps.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bayesian classification models for predicting compounds blocking hERG potassium channels

Abstract: Aim: A large number of drug-induced long QT syndromes are ascribed to blockage of hERG potassium channels. The aim of this study was to construct novel computational models to predict compounds blocking hERG channels. Methods: Doddareddy's hERG blockage data containing 2644 compounds were used, which divided into training (2389) and test (255) sets. Laplacian-corrected Bayesian classification models were constructed using Discovery Studio. The models were internally validated with the training set of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Liu et al . developed the Bayesian classification model using four molecular properties (MW, PSA, AlogP, and pKa_basic), as well as extended-connectivity fingerprints (ECFP_4), based on a dataset of 2,644 compounds including compounds tested on hERG in the literature and FDA-approved drugs, divided into a training set of 2,389 compounds and a test set of 255 compounds 19 . In addition, further validation was performed experimentally using an external data set of 60 compounds by Doddareddy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . developed the Bayesian classification model using four molecular properties (MW, PSA, AlogP, and pKa_basic), as well as extended-connectivity fingerprints (ECFP_4), based on a dataset of 2,644 compounds including compounds tested on hERG in the literature and FDA-approved drugs, divided into a training set of 2,389 compounds and a test set of 255 compounds 19 . In addition, further validation was performed experimentally using an external data set of 60 compounds by Doddareddy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This permits applications of automated electrophysiology in primary screening. In addition to experimental approaches, to predict the hERG liability of lead candidates early in drug discovery, numerical in silico methods have been developed [12][13][14][15][16][17][18] . Since experimental data from a large collection of structurally diverse compounds were yet available, models was usually based on the existing data of limited number of hERG inhibitors generated using different methods.…”
mentioning
confidence: 99%
“…These authors built two models using NB classification and recursive partitioning techniques and found that the NB model yielded better prediction results. Recently, Liu et al (2014) reported a model that was built by laplacsian-corrected Bayesian classification. Molecular fingerprints (extended-connectivity fingerprints) were used as descriptors, and the established models could identify the substructures as favourable or unfavourable for hERG channel blockage.…”
Section: Herg Toxicitymentioning
confidence: 99%